Pemberdayaan Pedagang Pasar Tradisional: Membangun Kesadaran Hukum untuk Keber-lanjutan Usaha - Haning, Semuel; Magdalen Rohi Riwu, Agustin Leni; Dillak, Marthen; Lestrari Dewi, Ni Putu Juliani (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to increase the legal awareness of traditional market traders, so that they can run their businesses legally and sustainably. Many traditional market traders do not understand their legal rights, such as business permits, tax obligations, and protection of their business premises. For this reason, this activity was carried out through counseling, training, and legal assistance. A total of 50 traditional market traders in [market name] participated in this activity. The results of the community service showed a significant increase in understanding among traders. Before the training, only 28% of traders understood the importance of business permits, while after the training, 85% of traders knew the correct licensing procedures. In addition, most participants also better understood their tax obligations and legal rights related to their businesses. Thus, this activity succeeded in increasing the legal awareness of traditional market traders which can help them manage their businesses better and reduce the risk of legal problems in the future. This community service also suggests the need to extend similar activities to other markets, as well as further cooperation between the government and educational institutions to strengthen the legal empowerment of traditional market traders.